HER-2 ultra-low breast cancer: exploring the clinicopathological features and prognosis in a retrospective study - Shi, Jiajie; Zhang, Liqiu; Geng, Cuizhi (Frontiers in Oncology, 2023)
Objective: To explore the clinicopathological features of patients with ultra-low expression of human epidermal growth factor 2 (HER-2) in breast cancer and its impact on prognosis Methods: Data from 1024 patients with primary breast cancer having HER-2 ultra-low expression from January 01, 2018, to December 31, 2018, were collected and analyzed retrospectively. The clinicopathological features and prognosis were compared using a chi-squared test or Fisher exact probability method. COX regression analysis and logrank test were used to explore the factors related to the postoperative 5-year survival rate. All analytical data were defined as statistically significant (P < 0.05).Results: Overall survival (OS) was higher in the HER-2 ultra-low group compared to the low expression group (P = 0.022). The tumor diameter, lymph node metastasis (LNM), and Ki67 expression were factors affecting DFS in the HER-2 ultra-low expression group (P < 0.05). The tumor diameter and LNM were risk factors affecting the OS (P < 0.05) in the HER-2 ultra-low expression group. LNM and Ki67 expression were risk factors affecting DFS (P < 0.05) in the HER-2 low expression group. LNM was considered an independent risk factor affecting OS (P < 0.05).Breast cancer with HER-2 ultra-low expression has differences in the clinicopathological features. Breast cancer with HER-2 low expression is more aggressive and has a worse prognosis. This study provides a reference to consider in the treatment of HER-2-low and -ultra-low expression breast cancer.